Ideación suicida en personas privadas de la libertad del centro penitenciario y carcelario de mediana seguridad de la ciudad de Riohacha. - Valencia Duque, Leidy Vanesa; Rangel Herazo, Alondra Emir (Universidad Antonio Nariño, 2024)
The present research of non-experimental design, descriptive scope and cross-section, aims to sociodemographic ally characterize the prevalence of people deprived of liberty with suicidal ideation in the medium security penitentiary and prison center of the special tourist and cultural district of Riohacha.